Isolation and identification of bacteria from the 2014 flood of Kota Bharu, Malaysia - Pwaveno Huladeino Bamaiyi; Nani Izreen, M.S; Khadijah, M; Nur Eizzati, B.H; Siti-Bainum, C.R; Norysyamimi Farhana, M.K.; Mohd Norfaizul, M.N (2015)
This study was carried out to elucidate the different bacteria present in flood water that affected different parts of Kota Bharu, Kelantan in December, 2014 and their antibiotic sensitivity. A total of 31 water samples in 50ml sterile containers were collected from 6 locations (5 samples from each of Taman Bendahara, Kampung Tok Sedang, KB clock roundabout, KB mall area, Tesco mall area and 6 samples from Jalan Kuala Krai) for bacteriological analysis by inoculating into blood agar and nutrient agar using sterile swabs. Different bacteria were identified from the cultures using colony morphology, differential/selective media and biochemical tests. Using the method of Flores et al (2009) and IDENTAX version 1.2 (2013), 38 species of bacteria were elucidated with 47% being zoonotic pathogens; 29% human pathogens; 13% Animal pathogens; 8% plant pathogens and 3% nonpathogenic bacteria. There was no significant difference (P>0.05) between the number of bacteria isolated from the different locations. Antibiotic sensitivity test indicates 78% of tested isolates were resistant to Penicillin G and Ampicillin; 67% were resistant to Amoxicillin. But, 89% of the tested isolates were susceptible to Tetracycline. This study indicate that flood waters come with a “cocktail” of bacteria that are capable of affecting humans, animals, plants and the environment. During floods human contact with the flood waters should be restricted as much as possible and prophylactic measures put in place against water and foodborne diseases that are common and rare in the tropics. Medical practitioners should consider bacterial resistance when prescribing medications during floods.